Task Commitment Analysis of Zenius Certified Independent Study Program Participants Batch II - Tsamara, Jihan Aulia; Khotimah, Husnul; Harsono, Yudi Tri (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Having task commitment is an obligation when dealing with problems in the workplace, which is specifically designed in an independent study program based on deep learning activity. The reason for this is that task commitment can encourage students to pay more attention to their work, as evidenced by discipline, consistency, and a strong work ethic. This article aims to reflect on the level of task commitment possessed by participants in Program Zenius Studi Independen Bersertifikat (PZSIB) Batch II through a quantitative descriptive review. The measuring instruments for this research use the Task Commitment scale. The participants in Program Zenius Studi Independen Bersertifikat Batch II demonstrated a high level of task commitment, with a percentage of 37.2%. As a result, the participants’ task commitment has an impact on achieving the main goal of the independent study program, which is to produce reliable and tough graduates in terms of competence and mentality in dealing with changing times, particularly in engaging with the world of work. Keywords: Independent Study; Task Commitment